New Insight into the Hydrogen Bond Effects in One of PRODAN Derivatives (1a) on Excited State in Methanol Solvent (Journal of Atomic and Molecular Sciences, 2019)
PRODAN derivatives would be a potential probe molecules. The hydrogen bond effects in PRODANderivatives on excited state in methanol solvent have some significance to explain their dynamic experiments.In this paper, we have presented a theoretical investigation into the influence of hydrogen bonding on thestructural and spectral properties of PRODAN derivative (1a) and methanol complexes using time dependentdensity functional theory. The focused work is the structures and vibrational spectra of PRODAN derivative(1a) hydrogen bonding compounds in methanol solvent. It was observed that the distances of hydrogenbonding between derivative and methanol molecule in complexes shortened in the $S_1$ state. The resultssuggested that the behavior and effect of hydrogen bonds increased in the excited proceed. In addition, theIR vibrational spectra of PRODAN-1a-MeOH complex occurred shift in the $S_1$ state. As a consequence, thehydrogen bonding of PRODAN derivative (1a) could play a role in the geometries and electronic spectra inexcited state.